Evaluación del Baculovirus Phthorimaea operculella (Zeller). - Puerta, Martha C.; Bustillo, Alex E.; Madrigal, Alejandro; Pérez, Luz E. (Instituto Colombiano Agropecuario, 2018)
Papa-Solanum tuberosum